2009
DOI: 10.1002/hep.23409
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention and fatty liver disease: The importance of both disrupting inflammation and reducing visceral fat

Abstract: hepatocyte-like cells. However, we then used human iPSCs while maintaining higher expressions of p21 than p53 in order to avoid tumorigenicity of the human iPSCs and to increase the value of the cells as research tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Increased lipid uptake by liver as a result of increased fatty acid flow from circulation coming from intra-abdominal fat deposition attributed to the increased food intake after estrogens withdrawal can primarily and partially explain hepatic fat accumulation. The portal/fatty acid flux theory suggests that visceral fat, via its unique location and enhanced lipolytic activity, releases toxic-free fatty acids, which are delivered in high concentrations directly to the liver [ 62 ]. However, the portal/fatty acid flux theory has been questioned with the observation that the bulk of portal vein free fatty acids originate from subcutaneous adipose tissue in overnight-fasted obese individuals [ 63 ].…”
Section: Estrogens Withdrawal In Animals: Central and Peripheral Ementioning
confidence: 99%
“…Increased lipid uptake by liver as a result of increased fatty acid flow from circulation coming from intra-abdominal fat deposition attributed to the increased food intake after estrogens withdrawal can primarily and partially explain hepatic fat accumulation. The portal/fatty acid flux theory suggests that visceral fat, via its unique location and enhanced lipolytic activity, releases toxic-free fatty acids, which are delivered in high concentrations directly to the liver [ 62 ]. However, the portal/fatty acid flux theory has been questioned with the observation that the bulk of portal vein free fatty acids originate from subcutaneous adipose tissue in overnight-fasted obese individuals [ 63 ].…”
Section: Estrogens Withdrawal In Animals: Central and Peripheral Ementioning
confidence: 99%
“…Currently, lifestyle intervention remains a major treatment approach for fatty liver [2,7]. Transient receptor potential vanilloid 1 (TRPV1) is able to sense a plethora of endogenous physical and chemical stimuli and transduce noxious heat and painful stimuli [12][13][14]26].…”
Section: Introductionmentioning
confidence: 99%
“…[37] Visceral fat, via its unique location and enhanced lipolytic activity, releases toxic-free fatty acids, which are delivered in high concentrations directly to the liver; therefore, excess intraabdominal fat deposition after estrogens withdrawal can primarily and partially explain hepatic fat accumulation. [38] Our results revealed that both caloric restriction and E 2 replacement were equivalent in decreasing liver TAG in comparison with OVX group. In line,…”
Section: Discussionmentioning
confidence: 50%